(3ebOeI aj GdeYGjfI GdEMUGFjIs - (3YHO GdQMef eMeO(B, (3CHh YeIs; (3GdMSjfj YHO GdHQ QGVj(B, s ((3GdQjGV(B:s (3OGQ GdeQjN ddfTQ(B,s, 1995)
(3HYV GdeaGgje GdEMUGFjI, GdeYGjfI GdYThGFjI GdHSjWI, GdeYGjfI GdWHjbjI GdYThGFjI, GdeYGjfI GdefJXeI, GdeYGjfI GdYfbhOjI, GdJbOjQ HGdfSHI Hjf eJZjQjf hHNW GdEfMOGQ hGdEQJHGW, GdeYGjfI GdeROhLI hJbOjQ MLe GdeLJeYs
(3HHdjhZQGajG(B: (3U(B.385 (3GdeUWdMGJ U(B.387 s
Keywords: (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s; (3GdEMUGA GdJWHjbjs